Research on dynamic cooperative technology of manned and unmanned networked information system - Haijun YE; Guofeng WANG; Zhiyong FENG (Tongxin xuebao)
To meet the needs of information security sharing and systematic dynamic cooperation of manned and unmanned formations and to build a dynamic communication network, firstly, a networked high-precision system time synchronization scheme was designed, using integrated network link management strategy and wireless channel on-demand preference algorithm, and the time synchronization accuracy could be up to 100 nanosecond level.Secondly, a data privacy protection and secure sharing solution for airborne networks was built, implementing communication data security of manned and unmanned formation, and analyzing and discussing the performance and security to prove that the proposed solution has a provable high security strength.Meanwhile, a dynamic cooperation model of manned and unmanned formation was designed to discover, authenticate and revoke each node in real time, perform legitimacy identity verification, optimize allocation scheme for multi-objective information acquisition through multi-machine collaborative construction, differentiated data was used to transmit synchronize data, save network resources, improve data transmission efficiency, and meet the demand of systematic cooperative operations.